Performance Improvement In Order To Improve Competitiveness Analysis On Supply Chain Management Integration Strategy Leather Industry In Tanggulangin - Rupiarsieh, M. Si; Santosa, Sutoro Haryo (Advances in Social Sciences Research Journal, 2019)
Supply Chain Management (SCM) is the over sight of material, information and finances as they move in a process from supplier to manufactures to consumer. Supply Chain Management involves coordinating and integrating these flows and base on Frohlich and Roy Westbrook (2001) there are 5 (five) types of integration: Inward-facing, periphery-facing, supplier-facing, customer-facing and out word facing. The variable of the type of integration are: access to planning systems, sharing production plans, join EDI access / networks, knowledge of inventory mix / levels, packaging customidation, delivery frequencies, common use of third – party logistics, with performance variables: financial perspective, customer perspective serta interval business process perspective. This research was investigated the correlation between the type of integration with the corporate performance in Financial Perspective, Customer Perspective and Internal Business Process Perspective. The data was get from the leather industry on Cluster Tanggulangin Sidoarjo. The result of the research as: There strong correlation between the type of integration quality of integration and industry performance. The benefit of the research is: there is possible to create the model of the correlation between the type of integration, quality of integration and the corporate performance that be able to choose the strategy of Supply Chain Management, to be used as inputs for policy makers to provide coaching and development of the leather industry in Sidoarjo Regency or another places with the same typology.